GEOCHEMICAL AND ISOTOPIC CONSTRAINTS ON THE GENESIS OF THE PERMIAN FERROPICRITIC ROCKS FROM THE MINO-TAMBA BELT, SW JAPAN - Ichiyama Y.; Ishiwatari A.; Hirahara Y.; Shuto K. (My University, 2006)
The Permian ferropicrite and picritic ferrobasalt occur in the Jurassic accretionary complexes of the Mino-Tamba belt as dikes intruded into the basaltic volcanic rocks. They are characterized by high MgO (11-27 wt.%), FeO* (16-20 wt.%) and HFSE (Nb = 24-86 ppm and Zr = 103-399 ppm) contents. Mineralogical and petrolographical evidences indicate that their unusual iron-rich nature is apparently magmatic in origin. The incompatible element contents and ratios indicate that the picritic ferrobasalt has close genetic kinship with the previously reported HFSE-rich, but iron-poor picrites, and that they were produced by the low degrees of partial melting of HFSE-enriched source material at high pressures (4-5 GPa). On the other hand, the ferropicrite may have been produced by the same degree of partial melting at a lower pressure, and subsequent olivine accumulation. The Sr and Nd isotopic signatures (87Sr/86Sr(i) = 0.70266 to 0.70329 and e{open}Nd(i) = + 5.7 to + 7.7) of these picritic and ferropicritic rocks are nearly constant and are equivalent to those of HIMU rocks, which require involvement of subducted oceanic crust material into their source region. Nevertheless, the ferropicritic melt cannot have been generated from the iron-poor picrite melt by crystal fractionation. Compared to the compositions of the melts obtained by some melting experiments, production of the unusual ferropicritic melts requires addition of an unreasonable amount of recycled basaltic component into the source mantle peridotite or partial melting at extremely high pressures. A possible source material for the ferropicrite is the mixture of the recycled Fe- and Ti-rich basalt (and/or gabbro) and mantle peridotite. Such a ferrobasalt occurs in the present ocean floor and also in some peridotite massifs as Fe- and Ti-rich eclogite bodies. The ferropicritic magma may have been derived from the Permian, deep mantle plume in an oceanic setting. The occurrence of the ferropicritic rocks and the HFSE-rich, iron-poor picrite in the Mino-Tamba belt implies that the greenstone-limestone-chert complexes in the Mino-Tamba belt may be fragments of an oceanic plateau formed by the Permian superplume activities in paleo-Pacific ocean and subsequently accreted to a continental margin through subduction process in the Jurassic time. © 2005 Elsevier B.V. All rights reserved.
Keywords: FERROPICRITE; HIMU MAGMA; MINO-TAMBA BELT; PERMIAN MANTLE PLUME; RECYCLED OCEANIC CRUST; SR AND ND ISOTOPES; Jurassic; Permian; Mesozoic::Jurassic; Мезозой::Юрская; Paleozoic::Permian; Палеозой::Пермская